Estudio comparativo enfocado en los estados de resultados de la Piladora "Muñoz" del Cantón Urdaneta dentro del periodo 2020 y 2021. - Murillo Barzola, Brittany Rossana (2022)
The purpose of this research project is to know the accounts of the income statements of Piladora Muñoz and carry out a horizontal analysis so that the variations that have occurred during the two periods referring to the year 2020 and 2021 can be determined. Companies must carry out an analysis of their accounts, because this is of vital importance when making decisions in order to determine what their strengths and weaknesses are, as well as knowing which decisions are appropriate to improve their finances, because of the finance depends on the stability of the company. A company that does not have stability only results in the decrease of all its capital, causing it to be closed without being able to make a movement. That is why it is always necessary to be cautious, to have knowledge of how our financial statements are, compare with previous years and know if the company has improved or the opposite.